The IMF's role in sovereign debt restructurings (European Central Bank (ECB), 2021)
The global recession caused by the COVID-19 pandemic and the resulting deterioration in many countries' public finances have increased the risk of sovereign debt crises. Although crisis prevention remains paramount, these developments have made it imperative to re-examine the adequacy of the current toolkit for crisis management and resolution, in a context where changes in the creditor base and in the composition of public debt instruments have brought about new challenges in terms of reduced transparency and additional barriers to achieving inter-creditor equity. This report focuses on the international architecture for sovereign debt restructurings (SODRs), as seen through the lenses of the International Monetary Fund (IMF or "the Fund") and with a special attention to the role that the Fund can play in facilitating orderly restructuring processes. It provides a set of findings and recommendations in relation to certain key elements of the Fund's lending framework that have important ramifications on SODR processes, namely debt sustainability assessments (DSAs), the exceptional access policy (EAP) for financing above normal access limits, and the criteria for lending to countries with payments arrears to private creditors (LIA) or official bilateral creditors (LIOA). It also considers other indirect channels through which the Fund can affect SODRs, including its support for enhancing the transparency and public disclosure of sovereign debt information, its collaboration with the Paris Club and the G20 debt-related initiatives, the promotion of contractual standards for sovereign debt, and the monitoring of relevant legislative developments.
Keywords: F34; F55; H63; 330; International Monetary Fund; sovereign debt; sovereign default; debtrestructuring regime